Adi Buddha dalam Candra Bhairawa Parwa - I Nyoman Wahyu Angga Budi Santosa; I Nyoman Darma Putra; I Wayan Suardiana (Perpustakaan Nasional RI, 2022)
This article contained the study of the Ādi Buddha in the Candra Bhairawa Parwa (CBP) it's one of the famous classical literature in Bali. The CBP is a part in a hipogram text of the Śiwāgama or famous title is Pūrwāgama Śāsana. The story of CBP is contained in sargah twelve. Śrī Candra Bhairawa is the main figure in this story, he practiced the ideal cult called Yoga Sanyāsa. In that devotion, he realized the Ādi Buddha; that is the highest primordial principle in other names Bajradhāra. This study used hermeneutics theory and method of interpretation by Paul Ricoeur to research Ādi Buddha in the CBP. Interpreted the text to know the origin, manifest, and concept realized to the idea of liberating in Yoga Sanyāsa and then to know Ādi Buddha cult in Bali.